Capturing ethylene glycol with dimethyl carbonate towards depolymerisation of polyethylene terephthalate at ambient temperature. Issue 23 (8th November 2021) - Tanaka, Shinji; Sato, Junichi; Nakajima, Yumiko
Abstract : A strategy of capturing ethylene glycol with dimethyl carbonate in the catalytic methanolysis of polyethylene terephthalate enabled depolymerization at ambient temperature. Abstract : Depolymerisation of polyethylene terephthalate (PET) via alkali metal alkoxide catalysed methanolysis efficiently proceeded at ambient temperature by capturing ethylene glycol (EG) with dimethyl carbonate (DMC), which biased the equilibrium toward dimethyl terephthalate (DMT) due to the thermal stability of ethylene carbonate (EC).